Specifications in the Actuarie’s Activities of the Insurance Companies in the Context of Digitalization - Grigorov, Simeon (Research Papers, 2022)
The specific features of the activity of actuaries in insurance are related to their important role in providing effective management systems in conditions of digitalization. Their reports, analyzes and recommendations are becoming even more necessary for insurance companies in the new digital age. Digitalisation poses serious challenges for insurance companies. They have to deal with the constantly changing information data sets that need to be processed, systematized, analyzed and summarized for the needs of management and state insurance supervision. Actuaries have extensive experience in summarizing and analyzing data from insurance operations, and their expert technical advice is extremely important for insurance companies. In the new digital ecosystems, actuaries provide expertise in modeling and optimizing forecasts, supporting for rapid, adequate and intelligent decisions, both in the field of insurance and in the field of management and administration of insurance, financial and business risks that accompany the activity of insurance companies.
Keywords: Actuaries; Insurances; Digitization